Nature exploitation and the disruption of dwelling in Fisher Stevens’s Before the Flood (2016): An ecocritical study - Muhammad Kharisma (Priviet Social Sciences Journal, 2026)
This study investigates the representation of nature exploitation and its disruption of human dwelling in Before the Flood (2016), a documentary film directed by Fisher Stevens. Two research questions guided the analysis: (1) how is nature exploitation represented in the documentary? and (2) how does this exploitation disrupt human dwelling? Using Garrard’s (2023) ecocriticism, particularly his concept of dwelling, this study applies a qualitative textual and cinematic analysis that examines dialogue, narration, and visual elements such as framing, montage, and sound. The analysis identified five major forms of nature exploitation depicted in the documentary: deforestation and resource extraction, fossil fuel dependence, industrial pollution, species extinction, and ecosystem damage. These forms are not merely isolated environmental harms but manifestations of anthropocentric and capitalist logics that reduce nature to an economic resource. The analysis further shows that this exploitation disrupts dwelling by threatening living space, displacing communities, endangering survival, and severing the everyday, embodied, and memory-laden relationship between humans and their environments. Scenes of flooding in Florida and Kiribati, air pollution in China, and crop failure in India illustrate how ecological destruction becomes, in Garrard’s terms, a crisis of belonging rather than only a crisis of habitat. The study concludes that Before the Flood frames the climate crisis as an ecological and existential rupture, positioning dwelling, understood as responsibility, care, and coexistence, as an ethical alternative to exploitation.